The Development of Local Wisdom Based Character Education Training Module - Puspoko Jati, Dionisius Heckie; Ismanto, Bambang; Sulasmono, Bambang S. (Journal of Education Research and Evaluation, 2019)
The development of local wisdom-based character education training modules is included in R & D research. This development research uses Sugiyono's development model with the following steps: (1) potential and problems, (2) data collection, (3) product design, (4) design validation, (5) design revision, (6) product testing and (7) product revision. In this study, trials were limited to 10 teachers. Data collection with interviews, questionnaires and validation. Next, the data analysis uses the normality test, hypothesis test, likert scale. The results of the data analysis obtained normal data, in which the hypothesis test concluded that there was a difference between the pretest and posttest training, the questionnaire results showed a value of 3.2 was said to be feasible. Furthermore, the validation test obtained the number 77, 5% in the category worthy of being tested. This module consists of modules for trainers and modules for participants along with plans for implementing training. Principals are advised to carry out training with local wisdom-based character education training modules, for teachers it is recommended to participate in training.